2004
DOI: 10.1111/j.1475-6773.2004.00323.x
|View full text |Cite
|
Sign up to set email alerts
|

America's Health Centers: Reducing Racial and Ethnic Disparities in Perinatal Care and Birth Outcomes

Abstract: Racial/ethnic disparities in certain prenatal services and birth outcomes may be lower in CHCs compared to the general population, despite serving higher-risk groups. Within CHCs, increasing first-trimester prenatal care use through perinatal care capacity may lead to further improvement in birth outcomes for the underserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
1
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 54 publications
3
40
1
1
Order By: Relevance
“…Our findings also support the notion that absence of racial disparities may be related to CHCs' culturally sensitive practices and community involvement – features that other primary care settings may lack and speaks to the success of CHC models in improving health outcomes for these most vulnerable patients 23, 33, 34…”
Section: Discussionsupporting
confidence: 78%
“…Our findings also support the notion that absence of racial disparities may be related to CHCs' culturally sensitive practices and community involvement – features that other primary care settings may lack and speaks to the success of CHC models in improving health outcomes for these most vulnerable patients 23, 33, 34…”
Section: Discussionsupporting
confidence: 78%
“…CHCs are mission-driven organizations that are widely viewed as providers of culturally competent care. Because of their specialized knowledge about treating underserved populations, they are thought to play an important role in eliminating racial and ethnic disparities in care quality and health outcomes (118). …”
Section: Primary Care Integration and The Health Of Latinosmentioning
confidence: 99%
“…41,42 Shi’s study of the 2003 National Health Care Disparities Report and the 2002 Community Health Center (CHC) User Survey found that patients of federally qualified health centers experienced fewer racial/ethnic and socioeconomic disparities in access and quality of care compared to patients of non-CHCs. 43 In a separate study of the Veterans Administration Health System, McGuire et al found that implementation of community-based primary care clinics decreased access disparities to VA services for homeless veterans with serious mental illness. 44 Rehman found that the ethnic disparity in BP control between African Americans and Whites was approximately 40% less at VA than at non-VA health care sites.…”
Section: Paths To Success For Eliminating Us Health Disparitiesmentioning
confidence: 99%